Avaliação da conservação hídrica em sistemas de produção de milho e soja, por meio da temperatura foliar, na região do SEALBA - Carvalho Filho, Abelardo Máximo de (2023)
Faced with future scenarios of climate change and water insecurity, soil preparation practices such as plowing and harrowing, still seen as essential for grain cultivation, can negatively affect agricultural production and the sustainability of crops, when applied continuously and in the long term. On the other hand, soil cultivation systems of a more conservationist nature have been identified as promoting improvements in their physical, water and chemical properties and, consequently, in plant production indicators. This study aimed to evaluate different grain cultivation systems regarding their ability to promote the conservation of available water in the soil profile for crops. The established hypothesis was that over time, conservationist systems are able to promote changes in the edaphic conditions of soils in coastal tablelands, giving them greater resilience to the occurrence of water stress commonly observed in the temporal window of grain cultivation in this ecoregion. To evaluate this hypothesis, leaf temperature was used, obtained using an infrared thermometer, and the leaf - air temperature difference was used as an indicator of the water status of the soil-plant system. For this purpose, an experimental area conducted 10 years ago with soybean and corn crops was used, with three cultivation systems being evaluated for each species: 1. Conventional tillage, 2. No-tillage farming and 3. No-tillage and rotation with Urochloa decumbens (in the case of soy) and for corn: 1. No-tillage farming, 2. No-tillage farming intercropped with Urochloa decumbens and 3. No-tillage farming intercropped with Urochloa decumbens in rotation with soy in no-tillage farming. The experimental arrangement was structured in randomized blocks, and the adopted statistical delineation was in randomized blocks with subdivided parcels. The leaf temperature and the difference between leaf and air temperature were analyzed for variance between treatments, blocks and over time, considering significance for P ≤ 0.05. Conservationist cultivation systems showed less oscillation in the transpiration process of crops and provided greater water resilience against abiotic stress factors. Soybean planted in no-tillage system, rotated with Urochloa decumbens and corn planted in no-tillage system, intercropped with Urochloa decumbens and rotated with soybean in no-tillage, in the long term modified the hydraulic properties of the soil and promoted greater storage of water in your profile.